Using desktop programs in the cloud environment - Ye. O. Modlo (Academy of Cognitive and Natural Sciences, 2013)
The introduction of cloud technology of various kinds is happening in many areas of life today, and one of the most important applications should be in education. Email, word processing, spreadsheets, presentations, collaboration, editing multimedia content, and more can all be used with a browser if the software and files are hosted in the cloud. This toolkit can be a free or very inexpensive alternative to expensive devices for students and faculty.